PENINGKATAN HASIL BELAJAR FISIKA MELALUI PENERAPAN PENDEKATAN INQUERY DENGAN ASESMEN AUTENTIK PADA SISWA KELAS XI IPA6 SMAN 6 BONE - MUHAMMAD TAMRIN (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Improving Physics Learning Outcomes Through the Application of the Inquery Approach with authentic assessments can improve Physics Learning Outcomes in class XI IPA6 SMA Negeri 6 Bone. The problem in this study is whether the application of the Inquery Approach with authentic assessments can improve Physics Learning Outcomes in class XI IPA6 students of SMA Negeri 6 Bone. The purpose of the research is to improve the learning outcomes of learning physics through the application of the inquiry approach with authentic assessments in class XI IPA6 students of SMA Negeri 6 Bone. The average physics learning outcomes of students in class XI IPA6 at SMA Negeri 6 Bone before giving the action (initial data) was 64.50, with a completeness level of 48.57% (Low). Physics Learning Outcomes of class XI IPA6 students of SMA Negeri 6 Bone who were taught using the Inquery Learning Model with Authentic Assessment in the first cycle were 75.80, the completeness level was 71.43% in the high category. Physics Learning Outcomes in the second cycle of class XI IPA6 students of SMA Negeri 6 Bone were 84.50 with a percentage of completeness 88.47%. The application of the Inquery Learning model with Authentic Assessment can improve Physics Results in Class XI IPA6 students of SMA Negeri 6 Bone. ABSTRAKPeningkatan Hasil Belajar Fisika Melalui Penerapan Pendekatan Inquery dengan asesmen autentik dapat meningkatkan Hasil Belajar Fisika pada siswa kelas XI IPA6 SMA Negeri 6 Bone. Masalah dalam penelitian ini adalah Apakah penerapan Pendekatan Inquery dengan asesmen autentik dapat meningkatkan Hasil Belajar Fisika pada siswa kelas XI IPA6 SMA Negeri 6 Bone. Tujuan penelitian yaitu untuk meningkatkan Hasil Belajar belajar Fisika melalui penerapan pendekatan Inquery dengan asesmen autentik pada siswa kelas XI IPA6 SMA Negeri 6 Bone. Rata-rata hasil belajar fisika siswa kelas XI IPA6 SMA Negeri 6 Bone sebelum pemberian tindakan (Data awal) sebesar 64,50, dengan tingkat ketuntasan ketuntasan yakni 48,57% (Rendah). Hasil Belajar fisika siswa kelas XI IPA6 SMA Negeri 6 Bone yang diajar dengan Penggunaan Model Pembelajaran Inquery dengan Asesment Autentik pada siklus I sebesar 75,80 tingkat ketuntasan 71,43% kategori tinggi. Hasil Belajar Fisika pada siklus II siswa kelas XI IPA6 SMA Negeri 6 Bone sebesar 84,50 dengan prosentasi ketuntasan 88,47%. Penerapan model Pembelajaran Inquery dengan Asesment Autentik dapat meningkatkan Hasil Fisika pada siswa Kelas XI IPA6 SMA Negeri 6 Bone.